If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) + 6 = 3(2x + -3) + 2x Reorder the terms: 4(-3 + 2x) + 6 = 3(2x + -3) + 2x (-3 * 4 + 2x * 4) + 6 = 3(2x + -3) + 2x (-12 + 8x) + 6 = 3(2x + -3) + 2x Reorder the terms: -12 + 6 + 8x = 3(2x + -3) + 2x Combine like terms: -12 + 6 = -6 -6 + 8x = 3(2x + -3) + 2x Reorder the terms: -6 + 8x = 3(-3 + 2x) + 2x -6 + 8x = (-3 * 3 + 2x * 3) + 2x -6 + 8x = (-9 + 6x) + 2x Combine like terms: 6x + 2x = 8x -6 + 8x = -9 + 8x Add '-8x' to each side of the equation. -6 + 8x + -8x = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 -6 + 0 = -9 + 8x + -8x -6 = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 -6 = -9 + 0 -6 = -9 Solving -6 = -9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7n-8-6-1n= | | 2x+12=-4 | | -12+12= | | -2a+2=-18 | | 7n-8-6-n= | | 2a^2-18a+28=0 | | 3x+12-2=4x+5-x | | 25x^4-225x^2=0 | | 4x-3(7-3x)=2x+4(5-2x) | | 2y-y=12-24 | | 5x+-1=21+3x | | 2x-10+5x=-3 | | 36xy^2-49x=0 | | z^2-49y^2= | | 10x-8=10x-8 | | 3x^2+2=6x | | 64=-x+7x+4 | | w-7= | | -39=x+6x+3 | | 3w^2-3= | | 6=-4x+7x+6 | | 32a^3=0 | | 2(3-x)+4=8-3(2x-5) | | -47=2x+2x-3 | | 3x-4(2-x)=3(x-2)-4 | | -5t=-25 | | 3x=-36 | | 9-4x=-39 | | 100x=5+3 | | -5x+8y=0 | | 3x-6+1=2x-8+x+13 | | 3(2x-3)+9=0 |